Interaction of the Mortar Flow with of a Mortar Pump’s Valve Ball - Kaczynski, Roman; Korobko, Bogdan; Vasyliev, Ievgen; Kivshyk, Anton (International Journal of Engineering and Technology, 2018)
The article deals with the process of interaction of the valve ball of a mortar pump with the mortar flow. The schemes of the working chamber with attached forces to its elements are drawn up. The hydrodynamic pressure is determined in the analytical form and as the results of the experiment. The structural parameters of the working chamber and the rheological parameters of the mortar are analyzed, which have the greatest influence on the magnitude of the hydrodynamic force.Â Â